Performance Analysis of Verification-Based Decoding for Packet-Based LDPC Codes overBinary Symmetric Channel - Zhu, B.; Huang, D.; Nordholm, Sven (IEEE Communications Society, 2009)
In this paper, we propose a statistical model to analyze the performance of verification-based algorithm (VA) for packet-based low-density parity-check (LDPC) codes over binary symmetric channel (BSC). In contrast to the analysis of VA in the literature, we propose to take the false verification into consideration. For a given ensemble of LDPC codes and channel parameters, the proposed analysis model gives an efficient way to find the average performance of packet-based LDPC codes with verification-based decoding. Through numerical results, we find that the proposed method can provide a close estimation of frame error rate (FER) for packet-based LDPC codes with verification based decoding over BSC for all crossover probabilities of practical interests.